Implementasi Pemikiran Ali Mustafa Yaqub Dalam Memahami Hadis Persoalan Busana Sosial Di Masyarakat - ., Mujtahid; Sadiyah, Dini; Assidiqi, Ali Hasan (Lisyabab : Jurnal Studi Islam dan Sosial, 2024)
Behind the many developed and educated societies, it turns out that there are still people who are far from this. Where in the community there is still early marriage, especially for women. With this being a counter to the current era and regulations that require marriage at least 18 years and compulsory education 12 years. The research method used is qualitative. The results show: 1) Parents' Views on Early Marriage Actually nothing wants to happen. Parents want their daughters to stay in school and work, but because of the economy, they marry early in the hope that their daughters can be useful and ease the burden on parents. 2) The existence of early marriage due to internal factors and external factors which include environmental, social, economic, cultural and so on. Of the many factors, economic and educational factors are the main ones. The economy with a small income and education that is indeed very far access reach, especially junior high school, makes the culture to marry off their daughters early.